2020
DOI: 10.31235/osf.io/t7ue9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Sexual Victimization: Findings From a National Representative Sample of Belgian Adults Aged 16-69

Abstract: Background: Sexual victimization is a major public health, judicial and societal concern worldwide. Prevalence studies on sexual victimization have mostly focused on female and student samples. Overall, nationally representative and comparable studies are still lacking.Methods:We applied a broad definition of sexual violence, including hands-off and hands-on victimization, and behaviorally specific questions to assess sexual victimization. Prevalence estimates were obtained after weighting the sample according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
1
1
Order By: Relevance
“…However, compared to an online study in the Belgian population aged 16 to 69 years using the same questionnaire, we found lower lifetime and past 12-months prevalence rates [34]. This decreased SV reporting with increasing age may adequately represent lower sexual victimisation rates in older adults or may be explained by several factors, such as reduced recall in general [35], reduced recall of negative events [36, 37], or higher mortality among people with a SV history [38, 39].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, compared to an online study in the Belgian population aged 16 to 69 years using the same questionnaire, we found lower lifetime and past 12-months prevalence rates [34]. This decreased SV reporting with increasing age may adequately represent lower sexual victimisation rates in older adults or may be explained by several factors, such as reduced recall in general [35], reduced recall of negative events [36, 37], or higher mortality among people with a SV history [38, 39].…”
Section: Discussioncontrasting
confidence: 56%
“…Although some studies reported physical force was more often used on older SV victims compared to younger victims, most studies did not report significant differences between younger and older victims regarding use of physical force as a coercion strategy [12]. Because our findings are similar to the coercion strategies identified by younger victims in Belgium [34], we assume that the coercion strategies used on older adults are similar to the ones used on younger victims and not as violent as believed [12].…”
Section: Discussionsupporting
confidence: 54%
“…However, a recent SV prevalence study in the Belgium population aged 16-69 years contradicts this hypothesis. 30 Another reason could be the use of BSQ to assess SV in our study. Research has shown that the use of BSQ leads to increased detection of SV in both men and women, but the impact may be even greater in men.…”
Section: Discussionmentioning
confidence: 96%